Perceived Social Support and Maternal Competence in Primipara Women during Pregnancy and After Childbirth - Sara Esmaelzadeh Saeieh; Mitra Rahimzadeh; Mansooreh Yazdkhasti; Shoukofeh Torkashvand (Shiraz University of Medical Sciences, 2017)
Background: Developing maternal competence in first time mothers has a significant impact on neonate's growth psychosocial development and neonates growth and psychological development. Social support can be an important element for becoming a new mother. We aimed to investigate how social support and maternal competence change during pregnancy and 4 months after it and examine the relationships among social support and maternal competence. Methods: This longitudinal study was conducted on 100 first time mothers attending health centers in Alborz city, Alborz Province, between February 2015 and January 2016. Data were collected through perceived social support questionnaire that consisted of 12 questions and Parenting Sense of Competence Scale consisting of 17 items scored based on Likert's scale. The collected data were analyzed by SPSS software, version 16. Repeated-measure test and Pearson's correlation coefficient were used. P<0.05 was considered significant. Results: Maternal competence significantly reduced during the study (P=0.008), while perceived social support did not show any significant reduction (P=0.286). A direct relationship was found between social support and maternal competent six weeks after childbirth (r=0.19, P=0.049), and also social support and maternal competence sixteen weeks after childbirth (r=0.23, P=0.01). Conclusion: Considering the reduction of maternal competency during the study, social support by healthcare providers may be helpful for the mothers' transition to motherhood, and midwives must design specific interventions to promote the sense of maternal competence and perceived social support in first time mothers.